2001
DOI: 10.1054/bjoc.2001.1948
|View full text |Cite
|
Sign up to set email alerts
|

HPV types and cofactors causing cervical cancer in Peru

Abstract: We conducted a hospital-based case-control study in Peru of 198 women with histologically confirmed cervical cancer (173 squamous cell carcinomas and 25 cases of adenocarcinoma/adenosquamous carcinoma) and 196 control women. Information on risk factors was obtained by personal interview. Using PCR-based assays on exfoliated cervical cells and biopsy specimens, HPV DNA was detected in 95.3% of women with squamous cell carcinoma and in 92.0% of women with adenocarcinoma/adenosquamous carcinoma compared with 17.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 14 publications
3
9
1
2
Order By: Relevance
“…Of the 4780 patients in the present study, 731 (15.29%) were infected with multiple HPV types; and of the 2260 women found to be infected with HPV in the study and control groups combined, 731 (32.35%) were infected with multiple HPV types. This is higher than in other studies, but the reported prevalence of multiple HPV infections varies widely, from 3.9% in Thailand [17], to 12.9% among women with squamous tumors in Peru [18], to 19.3% in Paraguay [19], to 32.2% in Korea [20], to 32% in Costa Rica [15], and to 34.3% in Mozambique [21]. These differences could be due to different rates of multiple infection in the various populations or to differences in the detection methods [22].…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Of the 4780 patients in the present study, 731 (15.29%) were infected with multiple HPV types; and of the 2260 women found to be infected with HPV in the study and control groups combined, 731 (32.35%) were infected with multiple HPV types. This is higher than in other studies, but the reported prevalence of multiple HPV infections varies widely, from 3.9% in Thailand [17], to 12.9% among women with squamous tumors in Peru [18], to 19.3% in Paraguay [19], to 32.2% in Korea [20], to 32% in Costa Rica [15], and to 34.3% in Mozambique [21]. These differences could be due to different rates of multiple infection in the various populations or to differences in the detection methods [22].…”
Section: Discussioncontrasting
confidence: 62%
“…This kit was chosen for its high rate (93.8%) of agreement with the commonly used Amplicor HPV test (Roche Molecular Systems, Alameda, California, USA) [9] and its good sensitivity, specificity, and reliability [10]. Its pool of HPV-specific primers and its microarray allow for DNA amplification and the detection of the following 21 HPV genotypes: 13 HR types (16,18,31,33,35,39,45,51,52,56,58,59, and 68), 5 LR genotypes (6, 11, 42, 43, and 44), and 3 types common in China (53, 66, and CP8304).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This detection result is in accordance with the relevance ratio (75%-96%) of HPV DNA obtained by other researchers who investigated cervical cancer patients [16][17][18][19] .…”
Section: Detection Of Hpv Infectionsupporting
confidence: 91%
“…This phenomenon indicates that genes belonging to HLA-B7 supertype possibly have the same or similar peptide epitope, unable to present HPV derived-antigen to T cell, leading to high cervical cancer risk. Our initial research on cervical cancer risk focused on HLA-A alleles to find out that HLA-A*0206 had a protective function against cervical cancer creation [29] , which proved that HLA-A*0206 can provide HPV16E7 [11][12][13][14][15][16][17][18][19][20] and the peptide epitope of E7 86-93 to provoke CTL killing function against the target cells.…”
Section: Discussionmentioning
confidence: 99%